2D Materials as Electron Transport Layer for Low‐Temperature Solution‐Processed Perovskite Solar Cells. Issue 3 (13th December 2020) - Shao, Hui; Ladi, Najib Haji; Pan, Han; Zhang, Xiao Li; Shen, Yan; Wang, Mingkui
Abstract : Low‐temperature solution‐processed perovskite solar cells (PSCs) based on organic–inorganic hybrid perovskites have emerged as a low‐cost and high‐efficiency thin‐film photovoltaic technology. The reported power conversion efficiency (PCE) of laboratory produced PSCs with an active area of less than 0.1 cm 2 has already exceeded 25%, which, however, decreases significantly to about 16% for a large device area of about 100 cm 2 . Therefore, the scalability has become one of the most significant limits on successful commercialization of perovskite photovoltaics. This includes realizing a homogenous and compact electron transport layer (ETL), facing with issues of defects, energy level mismatch, and high‐temperature annealing requirements. Therefore, an exploration of effective and low‐cost charge transport materials is crucial for scalable fabrication of highly efficient perovskite devices. The 2D materials have drawn wide attention in the PSC community with tunable bandgap and high carrier mobility. So far, the search for a wide range of novel 2D materials for use in PSCs has documented considerable progress; however, a lot remains to be done in this field. This review summarizes recent advancements in the application of emerging 2D materials as effective ETL, thus providing direction for future development toward efficient and large‐scale perovskite devices. Abstract : An electron transport layer is one of the essential components for most of the efficient perovskite devices. This review focuses on 2D materials as the electron transport layer in perovskite solar cells with tunable work function and high carrier mobility.